Rapid Determination of Salmonella in Samples of Egg Noodles, Cake Mixes, and Candies - Banwart, George J. (1969)
A glass apparatus system was compared with a standard enrichment broth-selective agar method to test samples of egg noodles, cake mixes, and candy for the presence or absence of salmonellae. The glass apparatus system used fermentation of mannitol, production of H(2)S, or motility, in conjunction with a serological test of flagellar antigens, to detect salmonellae. No salmonellae were detected in 173 samples of food products. Of these samples, 171 were found to be Salmonella-negative after 48 hr with the glass apparatus system. After 72 hr, the standard Salmonella procedure yielded 38 samples which produced Salmonella false-positive results on selective agars. Inoculation of samples with cultures of Salmonella showed that approximately one inoculated cell could be detected after 48 hr of incubation with the glass apparatus. The standard Salmonella test requires a minimum of 72 hr for completion. Compared with the standard Salmonella test, the glass apparatus system is a more rapid and simple system that can be used to determine the presence or absence of Salmonella in these food products.